The Role of The State in Capitalism and in A System of Cooperative Firms - Jossa, Bruno (Archives of Business Research, 2024)
The author criticises the marxist view of State power in capitalism and advances the thesis that within a truly socialist system the State would ultimately rise to the challenge of Hegel in terms of making it its task to serve the interests of the community at large. He set forth also the proposition that even in capitalistic systems the State might make it its task to further a gradual transition to socialism by peaceful means.